Approximation on the Quadratic Reciprocal Functional Equation - Abasalt Bodaghi; Sang Og Kim (Journal of Function Spaces)
The quadratic reciprocal functional equation is introduced. The Ulam stability problem for an ϵ-quadratic reciprocal mapping f:X→Y between nonzero real numbers is solved. The Găvruţa stability for the quadratic reciprocal functional equations is established as well.